'Invisible' mice reveal anatomical secrets. (15th November 2018) - Reardon, Sara
Technique that turns dead rodents clear uncovers surprising details about how the animals respond to injury. Technique that turns dead rodents clear uncovers surprising details about how the animals respond to injury. Gif showing a clip of panoptic vDISCO imaging revealing nerves (green) in a mouse